It's Not Only What You Say … How Communication Style and Team Culture Affect Audit Issue Follow-Up and Auditor Performance Evaluations - Proell, Chad A.; Zhou, Yuepin (Daniel); Nelson, Mark W. (The Accounting Review, 2022)
ABSTRACT Auditors work in hierarchical teams in which effective upward communication is critical to audit quality. In these teams, subordinates choose both the content, as well as the style, of their communications. We report survey and experimental evidence of the importance of communication style in the context of audit team culture. Our first two studies provide evidence that audit staff perceive assertive upward communication as risky and prefer to communicate passively, especially in less autonomous team cultures. Our third study provides evidence that audit seniors consider more follow-up procedures and rate staff higher when staff communicate assertively, especially in more autonomous team cultures. Combined, these studies indicate a disconnect between audit seniors, who reward and follow up more on assertive communication, and their staff, who prefer passive communication. Our results suggest the potential for audit quality improvements by better alignment of supervisor-subordinate communication-style preferences, especially in more autonomous team cultures. Data Availability: Contact the authors.